Reliability-Based Preventive Maintenance Scheduling for Raw Mill Equipment to Minimize Downtime at PT X - Alfadhlani Alfadhlani; Ahmad Zuhair; Prima Fithri (Department of Mechanical Engineering, Universitas Andalas, 2025)
PT X is one of Indonesia’s cement companies operating three active plants: Plant IV, V, and VI. Production data from 2022 and 2023 indicate that Plant V achieved only 79% and 86% of its production targets, with high downtime resulting from a reliance on corrective maintenance. This study proposes a preventive maintenance schedule to reduce downtime using the Reliability-Centered Maintenance (RCM) method for controlling critical components and an age-based replacement model for minimizing downtime. The analysis identified eight critical components in Raw Mill Machines 1 and 2, with reliability improvements ranging from 14% to 58%. Implementation of the proposed schedule resulted in increased machine availability by 5.1% and 4.65%, and system reliability improved by 33.71%. These findings demonstrate that RCM-based preventive maintenance effectively enhances operational performance.